Metatarsophalangeal Joint Reconstruction Using Talar Osteochondral Allograft following a Failed Dorsal Cheilectomy - Alexandria J. Lichtl; Kelly L. Vittetoe; Connie P. Friedman; Hardik P. Parikh; Christopher S. Lee (Case Reports in Orthopedics)
Dorsal cheilectomy is often used as a first-line surgical treatment for hallux rigidus; however, revision surgery is needed in nearly 9% of cases. One option for revision surgery is interpositional arthroplasty, which is designed to preserve joint motion and is favorable in young, active populations. This case discusses a young female patient with persistent, painful hallux rigidus and a large osteochondral defect despite prior dorsal cheilectomy. We performed an interpositional arthroplasty of the first metatarsophalangeal joint using an osteochondral allograft from the talus. At three-year follow-up, she had greatly improved function and was able to run without pain. To our knowledge, this is the first documented use of an osteochondral allograft from the talus in conjunction with metatarsophalangeal joint interpositional arthroplasty for treatment of hallux rigidus and a severe osteochondral defect. This technique introduces osseous subchondral scaffolding as well as mature hyaline cartilage into an osteochondral lesion, thereby reestablishing proper joint architecture and congruent articulation and ultimately improving range of motion and reducing pain. We present this technique as an experimental treatment option for restoring both the integrity and function of the metatarsophalangeal joint following trauma, osteochondritis dissecans, or prior operative failure in patients who wish to delay metatarsophalangeal joint fusion.